IoT based Smart Parking System - G, Anuradha; LS, Bhavana; HA, Bindushree; , Deeksha B Jadesh; KR, Darshan (International Journal of Computer Sciences and Engineering, 2025)
Advancement in industrialization leaves the parking management system out-dated. Traffic congestion at parking lots have become very often and people cannot even find a place to park their vehicles where first come first serve method is used. Traditional parking lots can be converted to smart ones by introducing Internet of Things (IoT) which in turn resolves the current parking issues. Problems such as, traffic congestion, limited car parking facilities and road safety can also be resolved by IoT. In this paper, the proposed Smart Parking system primarily consists of IoT module that is used to signalize the state of availability of each single parking space, the NFC technology is used to differentiate between registered and unregistered vehicles as they have separate parking areas, and a Mobile Application that provides the end users to view if the slots are occupied or empty. One of the main challenges in a college environment is students rushing to college just before the college begins. This causes a lot of congestion. Students end up parking in areas not reserved for parking or in such a way that it becomes difficult for others to remove their vehicles. Thus there is need for implementing a smart parking system in college environment which regulates all these issues using the above mentioned technologies.